Development of a Device-Assisted Nerve-Regeneration Procedure in Disruptive Lesions of the Brachial Plexus - Merolli, Antonio; Manunta, Maria Lucia; Mao, Yong; Masala, Gerolamo; Careddu, Giovanni Mario; Cubeddu, Francesca; Evangelisti, Maria Antonietta; Guida, Maria Letizia; Verardi, Caroline Antonia; Proietti, Claudio; Manunta, Andrea; D'Urso Labate, Giuseppe Falvo; Catapano, Gerardo; Polunas, Marianne; Louro, Pedro; Passino, Eraldo Sanna (Journal of Reconstructive Microsurgery, 2018)
Background We describe the development of a new surgical procedure to be used in the treatment of disruptive brachial plexus (BP) lesions. It is centered on an artificial device designed to assist nerve regeneration by providing a confined and protected environment. Nerve fibers can repair inside the device, while the adverse massive scar-tissue formation is limited to the outside of the device.Methods Steps in the development of the procedure were (1) definition of the rationale, (2) design of the device, (3) choice of an in vivo translational model, (4)refinement of the surgical procedure, and (5) performance of an in vivo pilot study as a proof of concept. An interdisciplinary team from several laboratories was involved in this work over a period of 6 years.Results Results showed the absence of significant scar tissue in the regenerate and the presence of myelinated fibers aligned proximodistally between the stumps. This surgical approach can be seen not only as a definitive treatment but also as an early examination and stabilization before some different surgery will be later performed. It may also be used as additional protection for traditional surgery like end-to-end coaptation.Conclusions We conclude that the availability of a suitable device-assisted early treatment, even if not to be considered definitive, could help in addressing the BP lesions at an earlier stage and this may improve the final outcome. Our evidence justifies further experimentation on this approach.
Keywords: biomaterials; brachial plexus; nerve regeneration